Flowering phenology and mating success of the heterodichogamous tree Machilus thunbergii Sieb. et Zucc (Lauraceae). Issue 1 (8th January 2015) - Watanabe, Shuntaro; Noma, Naohiko; Nishida, Takayoshi
Abstract: Heterodichogamy is defined as the presence of two flower morphs that exhibit male and female functions at different times among individuals within a population, and is regarded as an adaptation to promote outbreeding through enhanced intermorph pollination. In highly fragmented populations in which the morph frequency is biased, heterodichogamy may hamper population growth by reducing seed sets of the more numerous morph, and enhancing seed sets of the less numerous morph. In such situations, we hypothesize that individual plants experience greater seed sets if the opposite sexual morphs are nearby, and that individuals of a less numerous sexual morph have greater seed sets. After confirming heterodichogamy by observing flowering behavior and phenology, we tested these two hypotheses in a highly fragmented population of Machilus thunbergii, a putative heterodichogamous evergreen laurel tree. Our observations confirmed that M. thunbergii is heterodichogamous, consisting of two types of protogynous and bisexual flowers: a morning female (MF)–afternoon male morph and a morning male (MM)–afternoon female morph at the individual level. Sexual expression of the two morphs was highly synchronized and reciprocal. Investigation of seed‐set rates revealed greater rates of both morphs if the opposite morph was nearby. The less numerous sexual morph (MF) showed a greater seed‐set rate than the more numerous sexual morph (MM). Abstract : We reported heterodichogamy in Machilus thunbergii and investigated the effects of morph frequency on reproductive success.